KARAKTERISTIK EKSTRAK PEWARNA KULIT ANGGUR BALI (Vitis vinifera L. var. Alphonso Lavallee) PADA PERLAKUAN KONSENTRASI DAN pH PELARUT ETANOL - Ni Kadek Wiji Astuti; Ni Made Wartini; I Made Supartha Utama (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2022)
Grape fruit skins which contains high antioxidants are potential as a source of natural anthocyanin dyes. The extracted natural anthocyanin dye depends on the concentration of the solvent and the pH of the solvent. This study aims to determine the effect of solvent concentration and solvent pH in the extraction process on the characteristics of the Balinese grape skins dye extract from red wine by-products, and determine the best solvent concentration and solvent pH of the Balinese grape skins dye extract from the side product of red wine. This study were designed using a completely randomized design with two treatment factors. Factor I is the concentration of ethanol solvent, which is divided into three levels (70%, 80% and 90%). The second factor is the pH of the solvent which is divided into 3 levels (pH 3, 4 and 5). The data were analyzed using analysis of variance and then Duncan's multiple range test (DMRT 5%) was performed. The results showed that the concentration of ethanol solvent and solvent pH had a significant effect on yield, while the interaction had a significant effect on total phenol, total anthocyanin, antioxidant capacity, and IC50. The best characteristics of the extract were tested by the effectiveness index. The best extract was obtained in the treatment of ethanol solvent concentration of 90% with a pH of 3. In this combination of treatments, the yield characteristics of 26.91%, total phenol 5178.95 mg GAE /100 g, total anthocyanin 12363.9 mg/L, antioxidant capacity of 3657.31 mg GAEAC/100 g, IC50 25.11 ppm, L * value (brightness) 20.12, a * value (redness) 7.97, and b * value (yellowish) 5.71.